2018
DOI: 10.1002/anie.201810336
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Divergolides E and H

Abstract: This manuscript describes the first total syntheses of divergolides Eand H. The route employs atelescoped hetero-Diels-Alder and oxidative carbon-hydrogen bond cleavage as an entry into the central bridged bicyclic acetal unit. Additional key steps of the highly convergent route include ad esymmetrizing epoxidation, ac helation-controlled alkenylzinc addition, an amide formation between ah indered aniline and an acylating agent that is prone to ketene formation, and ac hallenging macrolactonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Specifically, site-selective cross-metathesis of ent - 3b with vinylpinacolboronate followed by iodination of the carbon–boron bond would deliver Fragment A . Modification of the alternate olefin via successive oxovanadium-catalyzed epoxide formation-hydrolysis-periodate cleavage would deliver Fragment B . The union of Fragments A and B by way of the triorganozincate , would furnish Fragment C , which upon Yamaguchi esterification and ring-closing metathesis (RCM) with Fragment D would generate the 14-membered macrolide of amphidinolide R. As prior studies suggest a thermodynamic preference for the 15-membered macrolide, , amphidinolides J and S are potentially formed via ring expansion of the 14-membered macrolide.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, site-selective cross-metathesis of ent - 3b with vinylpinacolboronate followed by iodination of the carbon–boron bond would deliver Fragment A . Modification of the alternate olefin via successive oxovanadium-catalyzed epoxide formation-hydrolysis-periodate cleavage would deliver Fragment B . The union of Fragments A and B by way of the triorganozincate , would furnish Fragment C , which upon Yamaguchi esterification and ring-closing metathesis (RCM) with Fragment D would generate the 14-membered macrolide of amphidinolide R. As prior studies suggest a thermodynamic preference for the 15-membered macrolide, , amphidinolides J and S are potentially formed via ring expansion of the 14-membered macrolide.…”
Section: Resultsmentioning
confidence: 99%
“…A second-generation version of this approach was employed to prepare analogs through a more convergent pathway. 115 Caplan showed that bridged ketals are accessible by incorporating the nucleophile into the aldehyde fragment rather than the diene fragment and applied this to the synthesis of divergolide E. 116 The hetero Diels-Alder between diene 215 and aldehyde 216 provided, after oxidation, dihydropyrone 217 . While the requisite protecting group on the phenol was not compatible with a one-step bridged ketal construction, a subsequent transformation led to the formation of this subunit and, eventually, the natural product along with the acyl-migrated isomeric natural product divergolide H.…”
Section: Quinone Oxidantsmentioning
confidence: 99%
“…This analysis defines complexity enhancement by increases in rings, stereocenters, unsaturations, heteroatoms, and molecular weight. We have used these metrics to guide a program directed toward the rapid generation of spirocyclic and bridged bicyclic acetals from structurally simple precursors . This report describes a new rearrangement reaction to form structurally complex spirocyclic ethers from acyclic precursors in which two rings and up to four stereocenters are generated.…”
mentioning
confidence: 99%